ANALSIS PENDAPATAN DAN PENGELUARAN RUMAH TANGGA PADA KAWASAN RUMAH PANGAN LESTARI (KRPL) DI KOTA PEKANBARU - Muhammad Syaifullah; Eliza Eliza; Suardi Tarumun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Sustainable Foods Household (KRPL) is a government program to improve food consumption based on the additional income of farmers. The purpose of this research are (1) to analyze the level of household income and farm income of farmers Sustainable Foods Household (KRPL) in Pekanbaru (2) to analyze the total expenditure and the proportion of household food to total expenditure of farmers Sustainable Food Household program in Pekanbaru. The method used in sampling is disproportionate random sampling method, the number of samples in the study was 62 samples member KRPL. Analysis of the data used is the analysis of farm income and the proportion of household expenditure analysis. The total amount of household income was Rp.194.845.500, which consists of the husbands’ income (Rp.137.050.000), KRPL farm incomes (Rp.8.685.500), the wives’ income (Rp.41.350.000), and other income (Rp7.760.000). KRPL program contribution to total family income amounted to 4.46%. Total amount of household expenditure were Rp.175.263.667, which consists of food expenditure Rp.97.876.067 and Rp.77.387.600 non-food expenditure. The proportion of household food expenditure KRPL agricultural groups were smaller than the proportion of non-food expenditure, which equal to 44.15%.Keywords: KRPL Program, Household Income, Household Expenditure, Pekanbaru City.